2011
DOI: 10.1103/physrevb.84.214404
|View full text |Cite
|
Sign up to set email alerts
|

Inducing and optimizing magnetism in graphene nanomeshes

Abstract: Using first-principles calculations, we explore the electronic and magnetic properties of graphene nanomesh (GNM), a regular network of large vacancies, produced either by lithography or nanoimprint. When removing an equal number of A and B sites of the graphene bipartite lattice, the nanomesh made mostly of zigzag (armchair) -type edges exhibit antiferromagnetic (spin unpolarized) states. In contrast, in situations of sublattice symmetry breaking, stable ferri(o)magnetic states are obtained. For hydrogen-pass… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 67 publications
1
63
0
Order By: Relevance
“…We fully relax all the GNMs until the maximum atomic force is less than 0.02 eV/Å, using a 2 × 2 × 1 k-mesh which leads to good convergence for the large unit cells. All the calculations are spin polarized, and the antiferromagnetic state is found to have the lowest energy for the systems considered here, in agreement with previous works 15,22,23 . We have checked the effects of vacuum spacing, and the 4 nm spacing is found to be well converged since further increasing it makes no change in all results.…”
Section: Methodssupporting
confidence: 79%
“…We fully relax all the GNMs until the maximum atomic force is less than 0.02 eV/Å, using a 2 × 2 × 1 k-mesh which leads to good convergence for the large unit cells. All the calculations are spin polarized, and the antiferromagnetic state is found to have the lowest energy for the systems considered here, in agreement with previous works 15,22,23 . We have checked the effects of vacuum spacing, and the 4 nm spacing is found to be well converged since further increasing it makes no change in all results.…”
Section: Methodssupporting
confidence: 79%
“…Our calculations have been carried out in the ballistic limit, which gives a reasonable first estimate for short devices whose dimensions are smaller than the various scattering lengths (important scattering mechanisms include the anharmonic phonon-phonon interactions, electron-phonon scattering, and electron-electron scattering). Also, spin polarization may turn important: recent studies have shown that one can have spin-splitting and a magnetic moment in triangular [77][78][79] antidots with pure zigzag edges. Above all, the most important future task is a systematic study of disorder effects.…”
Section: Discussionmentioning
confidence: 99%
“…In Figure 1 are calculated to be 1, 0, and 3 , respectively. Unlike graphene [48], the behavior of vacancies N in the magnetic properties does not follow Lieb's theorem because of the structural reconstructions with the N-N bond formation [49]. When the N-N bond formation is broken, the total magnetic moment increases.…”
Section: Atomic Vacancymentioning
confidence: 99%